The INNOVATION AND DEVELOPMENT LEARNING IN THE DIGITAL ERA - Apriyal Fakih Apriyal Fakih; Nuraini Nuraini; Yuli Setiowati (PT. Jurnal Center Indonesia Publisher, 2026)
The rapid development of information and communication technology (ICT) has changed the way information is accessed. The use of mobile devices, the internet, and various online learning applications is increasingly widespread. This demands innovation in learning methods to make it more relevant and interesting for learners. This article aims to identify ICT applications used for learning innovation and digital era learning models. The method used in writing this article is descriptive method and through literature study. The conclusion of this article is that there are three learning innovations that can be applied, namely: Project Based Learning (PjBl), Google Sites and Google Drive. And there are three digital era learning models, namely: Blended Learning is a combination of online and offline learning, Distant Learning and Mobile Learning (M-Learning) Mobile Learning is learning supported by wireless mobile technology (smartphones).